2022
DOI: 10.1017/jns.2022.86
|View full text |Cite
|
Sign up to set email alerts
|

The role of multi-dimensional women's empowerment in agriculture to improve the nutritional status of under-five children in rural cash crop producing, resource-limited settings of Ethiopia

Abstract: Little is known about the relation between the women empowerment in agriculture index, and health and nutrition outcomes among under-five children in Ethiopia. The study's objective was to examine women's empowerment in agriculture and its association with the nutritional status of children (6–59 months) in rural, cash crop producing, and resource-limited settings of Ethiopia. A community-based cross-sectional study was conducted employing 422 households; having women of reproductive age group and children und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…There is a breadth of research investigating women’s empowerment and child nutrition, with many studies demonstrating positive relationships between women’s empowerment (or indicators of empowerment) and various child nutrition outcomes [9]. Studies in Ethiopia have demonstrated positive relationships between domains of women’s empowerment and child nutrition, including a positive association between empowerment in agricultural household decisions and increasing women’s access to and control of economic resources and stunting reduction [31]; a positive association between the five domains of empowerment (as measured by the Women’s Empowerment in Agriculture Index [WEAI]) and children’s dietary diversity [32]; a positive association between survey-based women’s empowerment index (SWPER) social autonomy and decision-making scores and the odds of meeting children’s minimum dietary diversity [33]; a positive association between disempowerment in decisions about input into production and child stunting [34]; and an association between enhanced empowerment in socioeconomic status (i.e. increasing access to education, information, media, and promoting saving) and the likelihood of child stunting or wasting [35].…”
Section: Introductionmentioning
confidence: 99%
“…There is a breadth of research investigating women’s empowerment and child nutrition, with many studies demonstrating positive relationships between women’s empowerment (or indicators of empowerment) and various child nutrition outcomes [9]. Studies in Ethiopia have demonstrated positive relationships between domains of women’s empowerment and child nutrition, including a positive association between empowerment in agricultural household decisions and increasing women’s access to and control of economic resources and stunting reduction [31]; a positive association between the five domains of empowerment (as measured by the Women’s Empowerment in Agriculture Index [WEAI]) and children’s dietary diversity [32]; a positive association between survey-based women’s empowerment index (SWPER) social autonomy and decision-making scores and the odds of meeting children’s minimum dietary diversity [33]; a positive association between disempowerment in decisions about input into production and child stunting [34]; and an association between enhanced empowerment in socioeconomic status (i.e. increasing access to education, information, media, and promoting saving) and the likelihood of child stunting or wasting [35].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1, having more bargaining power enables women to negotiate for access to resources for themselves and their children, which in turn helps improve their children's nutrition outcomes, as argued in (48,49). Malnutrition and women's disempowerment still remain signi cant challenges in developing countries like Ethiopia (50,51,52). According to the Ethiopian Mini Demographic and Health Survey 2019 report, the prevalence of stunting and wasting are among the highest in the world (50).…”
mentioning
confidence: 99%
“…Malnutrition and women's disempowerment still remain signi cant challenges in developing countries like Ethiopia (50,51,52). According to the Ethiopian Mini Demographic and Health Survey 2019 report, the prevalence of stunting and wasting are among the highest in the world (50). Unfortunately, available studies showing the effect of women's empowerment on children's nutrition outcomes in Ethiopia have several drawbacks: they are not correctly weighted, missing values are not adequately considered, and/or are not generalizable to Ethiopia.…”
mentioning
confidence: 99%